Trash vortex : how plastic pollution is choking the world's oceans - Smith-Llera, Danielle, 1971- (Captured history. Science., 2018)
Explores how plastic is slowly collecting in the world's oceans, leaving vast swaths of debris on the surface and plastic particles in the water that harm the ocean's wildlife.